Potret Keteladanan Nabi Muhammad Dalam Membangun Perdamaian: Pandangan Hukum Islam Tentang Gerakan Radikalisme dan Makna Jihad - Mohammad Takdir (Postgraduate State Islamic Institute (IAIN) Metro, 2017)
This paper aims to elaborate portrait of the Prophet Muhammad’s leadership in building spirit of peace among Arabs. As the muslims leader, the Prophet Muhammad brought peace mission to uphold justice and to prevent some religious conflicts. This study used library research to understand that Islam is the religion of peace and reject violence as an instrument of justification. This study also used the descriptive method to know about the principles and values ​​of peace in Islam. The results of this study indicate that peace is the heart of religion that brings benefit to all mankind. The first, the movement of radicalism and terrorism was contradicted with religious doctrine and mission of the Prophet Muhammad in the improvement of morality of the people. The second, the jihad in Islam is a war too self defense (defense jihd) from any threat of the violence, not war frontally (ofensife jihd) without considering of humanity values. The third, the Medina Charter is one of the conflict resolution to build the spirit of peace and giving freedom to all groups to doing religious practices according to their respective beliefs. And the end, The Medina Charter became clear evidence of how the Prophet Muhammad has given full freedom to non-Muslims to coexistence with all the Muslims.